Ekspresi Artistik Anak Usia Dini melalui Aktivitas Musik Edukatif - Fajar Wahyuningtyas (Mahāsarā, 2026)
This study aims to analyze the forms and processes of artistic expression in early childhood through educative music activities within kindergarten learning contexts. Artistic expression in early childhood represents an essential dimension of holistic development, encompassing cognitive, motor, social-emotional, and creative aspects. This research employed a qualitative descriptive design involving 15 children aged 5–6 years. Data were collected through participatory observation during four music learning sessions, semi-structured interviews with the classroom teacher, and documentation. Data analysis followed an interactive model consisting of data reduction, data display, and conclusion drawing conducted continuously throughout the research process. The findings indicate that educative music activities—including singing, movement and song, rhythmic games, and simple instrument exploration—consistently facilitated the emergence of artistic expression. The most dominant form of expression appeared in movement and song activities, followed by vocal improvisation during singing sessions. Children demonstrated variations in intonation, spontaneous lyrical modification, expressive body movements, rhythmic alterations, and exploration of sound intensity. These expressions emerged when learning activities provided opportunities for exploration and improvisation within a play-based environment supported by teacher scaffolding. The study concludes that educative music activities function not merely as instructional tools but as creative spaces that nurture children’s artistic identity and self-expression. The findings suggest that early childhood educators should design music learning experiences that prioritize participation, flexibility, and imaginative engagement to optimize the development of artistic expression.